Decreased KAT5 Expression Impairs DNA Repair and Induces Altered DNA Methylation in Kidney Podocytes - Akihito Hishikawa (Cell Reports, 2019)
Summary: Altered DNA methylation plays an important role in the onset and progression of kidney disease. However, little is known about how the changes arise in disease states. Here, we report that KAT5-mediated DNA damage repair is essential for the maintenance of kidney podocytes and is associated with DNA methylation status. Podocyte-specific KAT5-knockout mice develop severe albuminuria with increased DNA double-strand breaks (DSBs), increased DNA methylation of the nephrin promoter region, and decreased nephrin expression. Podocyte KAT5 expression is decreased, whereas DNA DSBs and DNA methylation are increased in diabetic nephropathy; moreover, KAT5 restoration by gene transfer attenuates albuminuria. Furthermore, KAT5 decreases DNA DSBs and DNA methylation at the same nephrin promoter region, which indicates that KAT5-mediated DNA repair may be related to DNA methylation status. These results suggest a concept in which an environment of DNA damage repair, which occurs with decreased KAT5, may affect DNA methylation status. : Hishikawa et al. reveal that KAT5-mediated DNA repair is essential for podocyte maintenance and is related to changes in DNA methylation status. Decreased podocyte KAT5 expression may contribute to the pathophysiology of diabetic nephropathy, suggesting a therapeutic target. Keywords: podocyte, DNA damage repair, DNA methylation, diabetic nephropathy